Technology-Based Assessment Design for Islamic Education in the Merdeka Curriculum Era - Fardu Hasan; Nadira Bin Harun; Satriyani Fauzi; Irna Ali; Nurain Madjojo; Hasna Abdusamad; Samlan Ahmad; Abdurahman Hi Usman (International Journal of Multidisciplinary Research of Higher Education, 2026)
The digital transformation in education requires Islamic Education teachers to design assessments that are not only valid and reliable but also adaptive to the demands of 21st-century learning. This study aims to conceptually examine technology-based assessment designs aligned with the characteristics of Islamic Education, encompassing cognitive, affective, and psychomotor domains. Using a qualitative content analysis approach, data were collected through library research from books, journal articles, and relevant educational policy documents. Thematic analysis was conducted following Miles and Huberman’s framework, enabling the identification of key themes. The findings highlight four essential stages in digital assessment design: planning, instrument development, indicator and rubric construction, and result analysis. Platforms such as Google Forms, Quizizz, Kahoot!, Google Classroom, and Moodle provide efficiency, interactivity, and data analysis advantages, yet challenges remain in infrastructure limitations, low digital literacy among teachers, and risks of student misconduct. The implications recommend blended assessment strategies and strengthening digital competencies of Islamic Education teachers to ensure effective, authentic, and meaningful assessment practices in the Merdeka Curriculum era.